Public opinion on vaccines: the role of the scientific community in Italy. (20th October 2021) - Paladini, A; Regazzi, L; Castagna, C; Sapienza, M; Rosano, A; Ricciardi, W; Cadeddu, C
Abstract: Background: After rising for years, vaccination rates in Italy fell until 2015 because of unfounded safety concerns, abetted by some government and court actions. Public education and a 2017 law on mandatory vaccination have boosted rates since then. So far only a few papers have examined the correlation between beliefs and attitudes towards vaccines and the level of trust in the scientific community regarding vaccinations in the general population. Methods: Data were extracted from the Italian section of the last two editions of the European Social Survey (ESS), the first carried out between September and November 2017, the latter between December 2018 and March 2019. A descriptive analysis was conducted using survey data. In the two editions respectively 2, 626 and 2, 745 persons were interviewed. The main outcomes assessed was comparing the two surveys, so as to highlight the key changes in public opinion on vaccines. Results: In the 2017 edition, 19% of the respondents believed in the harmfulness of vaccines, out of them 29% did not even have trust in the scientific community while those confident in the safety of vaccines were 50%. In the 2019 survey, the proportion of those who believed vaccines to be harmful fell to 15%, the undecided rose to 15%, those opposed to the idea that vaccines are harmful became 63%, not responding people were 8%. Correspondingly, trust in the scientific community about vaccines has increased from 57% in the first survey to 70% in the last one. Conclusions: The scientific community and research bodies in the last years, in support of the Ministry of Health, have made a huge effort in the public debate on vaccines. This might play a role in increasing the public confidence in the safety of vaccines and the adherence to vaccination campaigns, changing the climate with regard to vaccination in general. Key messages: Italians changed their opinions on vaccines between two ESS surveys. The scientific community had a relevant role in the public debate on vaccines.